Place, Space & Power: From Under the Baobab Tree to a Fair Trade Co-operative-Women's Experiences in Shea Butter Production in Upper East Ghana - Boodhoo-Leegsma, Aissa (Université d'Ottawa / University of Ottawa, 2016)
Shea butter production in West Africa has been dominated by women and Northern Ghana specifically is a leading global producer. This thesis explores women’s perceptions of power, control and agency in the Ojoba Women’s Fair Trade Co-operative in Upper East Ghana. I add to the literature on women’s experiences with and in fair trade. I examine how the shea industry and the co-operative provide a marketplace for women and a space for women to co-operate and resist power structures. I emphasize how the Western language of empowerment builds substantially from pre-existing women’s networks and labour sharing practices in the agricultural context. The thesis evaluates the factors within Ojoba that contribute to women’s empowerment. To be ‘empowered’ in Ojoba reflects a variety of understandings, experiences and locations. Indeed “women’s empowerment” may misrepresent how the women are capable of building a physical and social space of safety, debate and growth.
Keywords: women's empowerment; women in agriculture; fair trade; Northern Ghana